DECISION SUPPORT SYSTEM TO SELECT CANDIDATES FOR LOAN USING TOPSIS - Rocky Tanaamah, Andeka; Prestiliano, Jasson; Djami, Elvin (Proceedings of KNASTIK, 2012)
Noticing the development of technology is developing rapidly increasing, companiesneed information systems that can support decision-making requirement. The existenceof a bank's lending activities is certainly one advantage for the bank including also thecustomers. In need of credit ratings as a material consideration for the prospectivecustomer before the bank decides to accept or reject the request of prospectivecustomers, this is done given the risk of uncollectible big enough. To assist indetermining a person's determination would be eligible for a loan then takes a decisionsupport system. This study aims to design and build a Decision Support System forSelecting Candidates for Loan using TOPSIS method. The criteria used in determiningthe decision, among others, ability to repay, collateral value, duration and status of thehouse. The benefits of this application are to provide an alternative form of reference tothe bank in determining the prospective customer who deserved the loan.